Synergistic Efficiency Between Types of Fungi and Algae for Wastewater Treatment - Al-Juburi, Wassein Jassim; Khalil, Mohammad Ibrahim; Al-Katib, Mira Ausamam (Journal for Research in Applied Sciences and Biotechnology, 2022)
The study aims to demonstrate the efficiency of the synergy between types of fungi and algae for wastewater treatment. Samples are collected from the waters of Wadi al-Kharazi inside the University of Mosul. Four genera of organisms, two sexes of fungi, and two sexes of algae are used for the purpose of reacting. Examinations are conducted for water treated with fungi and algae, as 8 treatments are used compared to the control treatment that contains water alone. The pH function, bicarbonate ions, and sulfates with the two elements iron and copper are measured. The results of the bicarbonate examination show that the best biological treatment is in the mixed culturing of the alga Spirogyra maxima and the fungus Trichoderma asperallum. The average concentration during the incubation periods is 162.8 mg.l-1 compared to the average control treatment ranging 204.9 mg.l-1. The results of the sulfate examination show a decrease in concentration for all treatments compared to the control treatment. The best biological treatment in the mixed culturing is between the alga Spirogyra maxima and the fungus Mucor racemosus, as the removal rate reached 48% compared to the average of the control treatment. Examinations have demonstrated the synergy between fungi and algae in increasing the efficiency of pollutant removal rather than using both separately.